2010
DOI: 10.1111/j.1442-9071.2010.02303.x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in response to botulinum toxin type A treatment between patients with benign essential blepharospasm and hemifacial spasm

Abstract: We have shown that patients with BEB have a shorter duration of effect with BTX and require more frequent BTX treatments than patients with HFS, highlighting that facial dystonias in patients with BEB is more challenging to manage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 16 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…These findings corroborate those published studies. 16,17,18,19,20,21,22,23,24 . The success rate in the present study was 94.73% when injections that did not produce any effect or produced a short-term or minor effect were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate those published studies. 16,17,18,19,20,21,22,23,24 . The success rate in the present study was 94.73% when injections that did not produce any effect or produced a short-term or minor effect were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…13,26,27 In another study, Cannon et al found that 90% of patients were satisfied with the effect of their last BTX-A treatment. 28 This satisfaction rate was higher in patients with HFS compared to the patients with BPS. 28 In our study, efficacy seemed to be better in BPS compared to HFS, but it was more stable in HFS after injections, whereas the efficacy trend showed up and down alterations in BPS (Graphic 1).…”
Section: Discussionmentioning
confidence: 87%
“…28 This satisfaction rate was higher in patients with HFS compared to the patients with BPS. 28 In our study, efficacy seemed to be better in BPS compared to HFS, but it was more stable in HFS after injections, whereas the efficacy trend showed up and down alterations in BPS (Graphic 1). This difference between the groups may be due to the small number of patients in the BPS group.…”
Section: Discussionmentioning
confidence: 87%
“…Facial dystonias may effectively be treated with periocular subcutaneous injection of botulinum toxin Vol:. (1234567890) [5,11,12]. These injections produce few local complications, such as ecchymosis, ptosis, or diplopia, and do not generally have systemic effects [13].…”
Section: Introductionmentioning
confidence: 99%